Galapagos en Canchalagueras . Galapagos in Canchalagueras - Almeida, Rosa Perez (Spain, 2007)
Verzio FF submission This film tells the memories, conflicts and wishes of an unknown village: San Cristobal, the Capital of the Galapagos. It is a story of human adaption to a context when that context is valued and protected internationally.